Overexpression of rice aquaporin OsPIP1;2 improves yield by enhancing mesophyll CO2 conductance and phloem sucrose transport. (11th December 2018) - Xu, Feiyun; Wang, Ke; Yuan, Wei; Xu, Weifeng; Shuang, Liu; Kronzucker, Herbert J; Chen, Guanglei; Miao, Rui; Zhang, Maoxing; Ding, Ming; Xiao, Liang; Kai, Lei; et al.
Abstract : OsPIP1;2 overexpression enhances rice growth and grain yield by facilitating leaf CO2 diffusion, which increases the net CO2 assimilation rate and phloem sucrose transport. Abstract: Aquaporins are involved in CO2 transport from the leaf intercellular air space to the chloroplast, which contributes to CO2 assimilation. However, the mechanism of CO2 transport by rice ( Oryza sativa L.) aquaporins is unknown. Here, we investigated the function of the aquaporin OsPIP1;2 in CO2 diffusion-associated photosynthesis and phloem sucrose transport. Moreover, the grain yield of rice lines overexpressing OsPIP1;2 was determined. OsPIP1;2 was localized to the plasma membrane and the relative expression of OsPIP1;2 was approximately 5-fold higher in leaves in the presence of an elevated CO2 concentration. Overexpression of OsPIP1;2 increased mesophyll conductance by approximately 150% compared with wild-type (WT) rice. The OsPIP1;2 -overexpressing lines had higher biomass than the WT, possibly due to increased phloem sucrose transport. In addition, the grain yield of OsPIP1;2 -overexpressing lines was approximately 25% higher than that of the WT in three-season field experiments, due to the increased numbers of effective tillers and spikelets per panicle. Our results suggest that OsPIP1;2 modulates rice growth and grain yield by facilitating leaf CO2 diffusion, which increases both the net CO2 assimilation rate and sucrose transport.